PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA DOSEN - Sugiarti, Endang (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
The existence of universities is determined by public trust, and lecturer performance is the answer. For this reason, universities need to improve the performance of lecturers through implementing quality teaching, research that results in innovation and community service. The research method uses quantitative, the number of samples is 52 Pamulang University lecturers with a simple random technique, the analysis method uses multiple linear regression, and the analysis stage consists of descriptive test, validity test, reliability test, classic assumption test, partial test, simultaneous test, and test coefficient of determination. The results showed that leadership style and motivation had a significant effect on performance. This finding confirms the importance of well-behaved leaders, proactive, flexible in communication, friendly in interacting, care about lecturers' careers, support the implementation of research and community service, so that the enthusiasm of lecturers is optimal and leads to increased performance. Keywords: Leadership Style, Work Motivation, Performance, Lecturer